Analysis of Pesantren Culture on the Growth of Community Economy (Case Study at Manahijul Huda Islamic Boarding School Year 2023-2024) - Egi Saparudin; Muhamad Nurman; Taryono Taryono (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This research examines how the culture of pesantren contributes to supporting the economic growth of the community, using Pondok Pesantren Manahijul Huda as the object of study. Pesantren, besides functioning as a religious educational institution, also plays a role as a center of economic activity through programs such as the Manah Festival and Manah Laundry. With a descriptive qualitative approach, data were collected through field observations, interviews, and documentation to provide a comprehensive picture of the economic role of the pesantren in its surrounding environment. The findings show that the cultural values alive in the pesantren also shape an open and participatory economic system, involving students, alumni, and the local community. The entrepreneurial initiatives developed in the pesantren also encourage the improvement of skills, independence, and the standard of living of the community. In this case, the pesantren acts as a driving force for social transformation by combining Islamic teachings with community-based economic empowerment.